Cornelius : the merry life of a wretched dog - Torices, Marc, 1989- (Drawn & Quarterly, 2025)
"Horrifying and hilarious, Cornelius the dog is a spectacular train wreck--you just can't look away. Cornelius is a fumbling loser, the butt of everyone's jokes. When his friend Alspacka is kidnapped, the subsequent criminal investigation turns into a dramatic and emotional ordeal, upending Cornelius's life. Torn between his desire to be a writer and his immense guilt over his cowardly role in Alspacka's abduction, Cornelius is a classic Faustian figure: an aspiring artist so hungry for success that he will pay any price."--Amazon.com.